Do software payments amount to royalties? Tracing the answer in the context of the engineering analysis case and proposing an alternative model - Gururaj Devarhubli; Yogendra Batra; Alaukik Shrivastava (Cogent Social Sciences, 2023)
After almost two decades of litigation characterizing software payments for income taxation, the Hon’ble Supreme Court of India delivered a judgment on a batch of over a hundred appeals before it. The judgment respited the taxpayers. The present article analyzes the various arguments presented by the taxpayers and the Revenue Department and tests their applicability on the touchstone of International and Indian legal provisions and the established understanding of copyright law. The article concludes that the impact of copyright law on taxation cannot be avoided and any exploitation of copyright leading to income-generation is subject to tax. However, instead of bypassing copyright laws, a correct interpretation of the nuances of copyright laws would lead to more effective and less debilitating results.